Strategic Maintenance Boosts Global Power Plant Efficiency and Safety: Pemeliharaan Strategis Meningkatkan Efisiensi dan Keselamatan Pembangkit Listrik Global - Maulana Zulfikar, Raihan; Mulyadi, Mulyadi (Universitas Muhammadiyah Sidoarjo, 2024)
This study addresses the maintenance of the Main Cooling Water Pump (MCWP) in Gas and Steam Power Plants, crucial for performance and sustainability. Existing practices often lack a comprehensive approach, integrating routine inspections with proactive maintenance strategies. We aimed to develop a maintenance framework that improves operational efficiency, safety, and environmental sustainability. Over a 12-month period, data from various facilities indicated that our holistic approach increased pump efficiency by 15%, reduced downtime by 20%, and enhanced compliance with safety and environmental standards. These findings underscore the importance of integrated maintenance practices in responding to evolving industry challenges and regulations. Highlights: Holistic maintenance approach vital for MCWP performance. Safety compliance crucial for personnel and asset protection. Maintenance enhances efficiency and sustainability efforts. Keywords: Maintenance, Main Cooling Water Pump, Energy Efficiency